ChemInform Abstract: Intermolecular Noncovalent Hydroxy‐Directed Enantioselective Heck Desymmetrization of Cyclopentenol: Computationally Driven Synthesis of Highly Functionalized cis‐4‐Arylcyclopentenol Scaffolds. Issue 29 (June 2016) - de Oliveira Silva, Juliana; Angnes, Ricardo A.; Menezes da Silva, Vitor H.; Servilha, Bruno M.; Adeel, Muhammad; Braga, Ataualpa A. C.; Aponick, Aaron; Correia, Carlos Roque D.
Abstract: The Heck—Matsuda desymmetrization of 3‐cyclopenten‐1‐ol is studied by both computational and synthetic means.